(untitled) (Research, Society and Development, 2021)
The strengthening of the conjecture for coping with the pandemic by COVID-19 in the context of Primary Health Care highlights the need for tools to strategically streamline care, promoting quality of care by organizing the flow of patients according to resources available in the approach of the flu syndrome. Thus, this study aims to report the operational experience of the Fast-Track methodology as a tool that promotes quality of care in health services to fight the pandemic by COVID-19. With this insight, a descriptive study, with a qualitative approach, of the experience report type, was carried out on the operation of the Fast-Track methodology as a care quality tool. For the proper functioning of health services, the implementation of the methodology ensures agility in care, especially in times of large assistance flows. However, to achieve the assurance of quality and safety of care, it is necessary to follow the operational standard in methodological rigor, for the quality of care. In this sense, health services start to receive a different look for the care and observation of patients. Therefore, and put in visibility by the effectiveness and agility of the functioning of health services, the Fast-Track methodology stands out in relation to the reception of suspected cases in the context of Primary Health Care. it is expressed by feelings that permeate satisfaction with the reception of the final classification and outcome of cases, as well as encouraging the search for improvements in management and care.